The mythical Bill : a neurological memoir - McAuliffe, Jody, 1954- (University of Iowa Press, 2013)
Part medical mystery, part war story, and part social and family history, this is the story of how one man's physical and mental pain radiates outward into the life and mind of each member of his family. Weaving together diary entries, correspondence, and scrupulous research, the author examines her father's life before, during, and after WWII, seeking answers to the questions of what really happened to Bill McAuliffe and what caused his disintegration. His initial postwar diagnosis was torticollis: a condition of persistent involuntary contraction of the neck muscles, causing the head to be twisted to an abnormal position. But torticollis was only the beginning of Bill’s suffering and his daughter’s efforts to understand it. The condition becomes a metaphor for things that refuse to fall into place: the body not in accord with the mind, the head that turns away from reality.